2012
DOI: 10.1002/cne.23153
|View full text |Cite
|
Sign up to set email alerts
|

Birth of neural progenitors during the embryonic period of sexual differentiation in the Japanese quail brain

Abstract: Several brain areas in the diencephalon are involved in the activation and expression of sexual behavior, including in quail, the medial preoptic nucleus (POM). However, the ontogeny of these diencephalic brain nuclei has not to this date been examined in detail. We investigated the ontogeny of POM and other steroid-sensitive brain regions by injecting quail eggs with 5-bromo-2-deoxyuridine (BrdU) at various stages between E3 and E16 and killing animals at postnatal (PN) days 3 or 56. In the POM, large numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 112 publications
3
33
0
Order By: Relevance
“…In juvenile quails, very few PCNA-ir cells were observed in the mesopallium and caudal part of the nidopallium adjacent to the lateral ventricles. Similarly, Bardet et al (2012) reported the presence of a few PCNA and BrdU labelled cells in the quail pallium and concluded that these could be slow cycling progenitors. Alternatively, the presence of PCNA-ir cells in the parenchyma may not be related to cell proliferation but to DNA repair in mature neurons as proposed by Essers et al (2005).…”
Section: Age-related Changes In Pcna and DCX Expression In Different mentioning
confidence: 92%
See 4 more Smart Citations
“…In juvenile quails, very few PCNA-ir cells were observed in the mesopallium and caudal part of the nidopallium adjacent to the lateral ventricles. Similarly, Bardet et al (2012) reported the presence of a few PCNA and BrdU labelled cells in the quail pallium and concluded that these could be slow cycling progenitors. Alternatively, the presence of PCNA-ir cells in the parenchyma may not be related to cell proliferation but to DNA repair in mature neurons as proposed by Essers et al (2005).…”
Section: Age-related Changes In Pcna and DCX Expression In Different mentioning
confidence: 92%
“…In galliformes such as quails and chicks, neurogenesis starts at about 16-30% of hatching time and is presumed to be complete for the medulla by 30%, the tectum by 50% and the telencephalon by 50% of hatching time (Mezey et al 2012). However Bardet et al (2012) reported that neurons in most brain areas in the quail except for the telencephalon and the cerebellum are born and become post-mitotic before embryonic day 6 (E6). Even if neurogenesis persists throughout life in the telencephalon of adult birds, the bulk of neurons in this part of the brain are produced before E6 in quails (Bardet et al 2012) and E7-E9 in chicks (Tsai et al 1981).…”
Section: Ontogenetic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations